The use of iron-fortified wheat flour to reduce anemia among the estate population in Sri Lanka - Nestel, Penelope; Nalubola, R.; Sivakaneshan, R.; Wickramasinghe, A. R.; Atukorala, S.; Wickramasinghe, T. (IMR Press, 2004)
The use of flour fortified with 66 mg/kg of electrolytic or reduced iron to reduce the prevalence of anemia was determined in a two-year, double-blind, controlled trial. The trial was conducted in Sri Lanka among preschoolers between 9 and 71 months old, primary schoolers 6 to 11 years old, and nonpregnant women. At baseline, 18.4% of the preschoolers had low hemoglobin (Hb) concentrations. Neither electrolytic nor reduced iron had an effect on Hb concentration among preschoolers. Only 7% of the primary schoolers were anemic at the start of the trial and, again, fortification had no effect on Hb concentration. Twenty-nine percent of women had a low Hb at outset and there was no evidence that fortification had an effect on Hb in this group. The findings from this study suggest that fortification of flour with electrolytic iron or reduced iron was not beneficial in reducing anemia in this population. This was probably due to the low prevalence of anemia and low bioavailability of the fortificant iron. Fortification with either iron fortificant was acceptable.